CYTOKINE LEVELS IN HIV-INFECTED CHILDREN WITH VIRAL DIARRHEA (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Diarrhea occurs in 30-60% of patients with HIV in developed countries, while in low- and middle-income countries, nearly 90% of people living with HIV suffer from diarrhea. Intestinal infections are considered the primary cause of diarrhea in these regions [Wondmieneh A, Gedefaw G, Alemnew B. Intestinal parasitic infections and associated factors among people living with HIV/AIDS in Ethiopia].